BUSINESS PLAN - Sahroni, mahammad; Rafif Waluyo, Muhammad Rakha; Rosalina, Sinta (Journal for Management Student (JFMS), 2022)
To start a business, a mature Business Plan is needed, one of which is the ability to pour bright ideas or ideas that are creative and innovative and have high economic or commercial value into a mature and realistic Business Plan. The importance of a Business Plan becomes absolute when we are going to run or build a business, because planning itself is the same as a map and compass to run an optimal business, with a careful planning we can set the main business goals, priorities, and set cash flow. Good business planning will make the chances of success in business even greater. Good business planning indicators include: Simple (Convenient and practical) to do; Specific in its time, personnel, and budget; Realistic in goals, budgets, and achievement targets, and complete or complete all the elmens. .